Coordinated target tracking of two UAVs based on game theory approach and Lyapunov guidance vector fields. Issue 1 (June 2021) - Shi, Hanran; Lu, Faxing; Qi, Jiangxin; He, Haotian
Abstract: Considering the problems of the lack of tracking the intelligent target, which is "smart" enough to escape from the detection by maximizing the estimation error in the current tracking methods by multi-UAVs, a cooperative control method for tracking intelligent target by two UAVs is proposed based on Lyapunov guidance vector field. The mathematical model of an intelligent target is established. According to the multi-UAV distributed intelligent target state fusion estimation method, the target state information is obtained to control two UAVs to circle the target through the Lyapunov guidance vector method. The simulation results demonstrated that the method enables two UAVs to track the intelligent target stably and improve the intelligent target's positioning accuracy effectively